The transition to living in a university residence: first year students perceptions in this regard - Adams, Carima (Department of Social Development, 2024)
This study explored first year students' perceptions of the transition to living in a university residence at the University of Cape Town. It explored the positive and challenging aspects of adjusting to living in a residence as well as what support participants had received with this transition. Participants made recommendations to the university to assist students with the transition to living in a residence and to incoming first year students with regards to managing the transition to residence living. The research was conducted using a qualitative approach, more specifically an exploratory design. Nineteen participants who were first year students and had moved into a residence were purposively selected. They were interviewed online and in-person using a semi-structured interview schedule. The data obtained were analysed using qualitative methods. The findings of this study highlighted the experiences that first year students had when adjusting to residence life. Positive aspects in their transition were the convenience that residence offered, being independent and having freedom, flourishing, and having a roommate. Challenges included loneliness, catering in residences, the schedule of the residences and living with others. Areas of support that participants identified that assisted with their transition to residence were support from sub-wardens, mentors, and peers. Participants made recommendations to the university to assist students with the transition to living in a residence and this included improvements in the residence and increased support for students. Participants recommended that incoming first year students who are moving into a residence should make use of support services, prioritise their studies and focus on their selfdevelopment. Further recommendations were made to The Department of Student Affairs at UCT and recommendations for future research are included.